Monocrystallization upgrading reconstruction method of highly-degradable layered nickel-cobalt-manganese positive electrode material
The high-energy molten salt method efficiently regenerates waste lithium-ion battery cathode materials by optimizing lithium replenishment and defect repair, addressing industrial application challenges and achieving superior performance.
Patent Information
- Application Number
- CN202410939768.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-15
AI Technical Summary
Existing methods for recycling waste lithium-ion battery cathode materials, particularly layered nickel-cobalt-manganese materials, face challenges such as cumbersome pretreatment steps, inefficient lithium replenishment, and environmental impact, with the eutectic molten salt method requiring optimization for industrial application.
A high-energy molten salt single crystal reconstruction method that includes lithium replenishment under high temperature conditions, using a mixture of LiOH, Li2CO3, and KCl to ensure a stable molten salt environment, facilitating efficient defect repair and regeneration of the cathode materials.
The method effectively restores the structural and electrochemical stability of degraded cathode materials, reducing reaction time, minimizing environmental impact, and achieving performance comparable to commercial standards with improved cycle stability and capacity retention.
Smart Images

Figure CN119133669A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of recycling and regeneration of waste ternary lithium-ion battery positive electrode materials, and specifically relates to a single crystal upgrading and reconstruction method for highly degradable layered nickel-cobalt-manganese positive electrode materials with the assistance of high-energy molten salt. Background Art
[0002] With the rapid development of the new energy industry, especially the increasing popularity of electric vehicles, ternary lithium battery cathode (NCM) is increasingly dominating the field of lithium battery energy storage. The penetration rate of lithium-ion batteries in the new energy field continues to increase, the market size is also expanding, and supply is in short supply. Under this development situation, the prices of major metal elements in lithium-ion batteries are steadily increasing; in addition, the life of lithium batteries is generally 5-8 years. With the advancement of large-scale applications, the amount of battery retirements will reach a peak in the next few years, and untreated waste batteries may cause serious damage to the environment. Therefore, whether from the perspective of economic value or environmental protection, the recycling of waste lithium-ion batteries has become very urgent.
[0003] At present, the recycling technologies for waste batteries mainly include indirect recycling based on pyrometallurgy and hydrometallurgy and direct recycling based on regeneration and repair. Although pyrometallurgy has achieved large-scale industrialization, it has high energy consumption and produces a large amount of CO, CO2 and dust during the recycling process, causing serious pollution to the environment. In contrast, hydrometallurgy has less waste gas emissions, mild reaction conditions, and high metal recovery rates, but the cost of organic extractants is high, the recycling steps are complicated, and the organic waste liquid produced is not environmentally friendly.
[0004] In view of the obvious shortcomings of the above-mentioned indirect recycling methods at this stage, direct recycling, as an efficient and environmentally friendly recycling method, has become the research focus of scientific researchers. The standard definition of lithium-ion battery disposal is a capacity loss of more than 20%, which means that there has been obvious lithium loss and irreversible structural phase change in the battery, but the main structure of the battery has not been destroyed, which provides a theoretical basis for direct repair technology. Direct recycling aims to restore battery performance to the level before use by repairing various defects in the positive electrode material. The main ways of positive electrode failure include loss of active lithium ions, particle cracks, cation mixing, and changes in surface phase structure. The regeneration methods that have been proven to effectively repair positive electrode defects are mainly solid-phase sintering, hydrothermal method, electrochemical method and eutectic molten salt method. Among them, the eutectic molten salt method is considered to be the most promising direct regeneration method due to its clean, efficient and simple operation.
[0005] The advantage of the eutectic molten salt method is that it accelerates the medium transfer during the lithium replenishment process through a uniform and stable liquid phase environment, making the Li +Under molten conditions, the missing lithium vacancies in the positive electrode material can be effectively compensated. At the same time, the volatilization of the molten salt under high temperature conditions promotes the single crystal transformation of the regenerated positive electrode particles, thereby improving the electrochemical stability and structural stability of the regenerated samples.
[0006] Although the direct regeneration of layered nickel-cobalt-manganese cathode materials by the molten salt method has been widely confirmed, the following problems still need to be further optimized before large-scale industrial application can be achieved: (1) The object of molten salt recycling is only the active material of the battery cathode, so cumbersome pretreatment steps are required before recycling; (2) In order to ensure a uniform and stable lithium replenishment molten salt environment, an excess of eutectic molten salt is usually added. How to efficiently remove the residual molten salt after the lithium replenishment is completed is a challenge; (3) When lithium replenishment is only performed at the eutectic point temperature, the ideal regeneration effect cannot be obtained; and when the temperature rises, the molten lithium salt will evaporate rapidly and the lithium replenishment molten salt environment will be destroyed; in addition, when the amount of molten salt added is small, the regeneration requirements cannot be met, and excessive use of molten salt will inevitably cause resource waste. Therefore, how to determine an optimal lithium replenishment condition is also a difficult problem that needs to be overcome before the industrial application of the eutectic molten salt method.
[0007] In summary, developing and optimizing a more efficient, convenient and universal recycling method for upgrading and reconstructing lithium battery positive electrode molten salt is of great significance for the recycling of waste batteries. Summary of the invention
[0008] In order to solve the above problems, the present invention proposes a molten salt single crystal reconstruction method suitable for achieving high-level regeneration under high temperature conditions after improvement and optimization based on the existing eutectic molten salt method. This method can not only completely eliminate various defects in highly degraded positive electrode materials, but also, compared with the original polycrystalline particles, the regenerated single crystal structure can further alleviate the volume phase change of the regenerated particles during the charging and discharging process, reduce the generation of cracks, and greatly improve the cycle stability of the battery.
[0009] The technical solution adopted by the present invention is as follows:
[0010] A method for upgrading and reconstructing a single crystal of a highly degradable layered nickel-cobalt-manganese cathode material with the assistance of a high-energy molten salt comprises the following steps:
[0011] Step S1, after the waste ternary lithium-ion battery is completely discharged, the aluminum current collector coated with the positive electrode active material is separated by mechanical disassembly, and the aluminum foil can be removed by simply sieving after crushing with a pulverizer to obtain a positive electrode powder with degraded performance;
[0012] Step S2, mixing the obtained positive electrode powder with the selected molten salt in proportion, grinding with a ball mill to ensure that the molten salt and the recovered powder are evenly mixed, and then performing a lithium replenishment process under high temperature conditions, while the residual binder and conductive agent impurities in the positive electrode powder can also be effectively removed after thermal decomposition;
[0013] The lithium replenishment heating conditions are to heat the temperature to 600°C and keep it for 2 hours, then keep it at 910-930°C for 4-6 hours, the heating rate is 4°C / min, the gas atmosphere is air, and the gradient heating method can provide a more stable lithium replenishment molten salt environment.
[0014] Step S3, after the lithium supplementation is completed, the sample is centrifuged, washed and dried, and then heat-treated in an oxygen atmosphere to repair the impurity phase structure that may exist on the particle surface.
[0015] Furthermore, the complete discharge process in step S1 is carried out in a Na2SO4 solution with a concentration of 5%-10% and the immersion time is 48-72h;
[0016] And / or, after the aluminum foil is initially removed by sieving through a 400 mesh in step S1, the positive electrode powder is alkaline-soaked with a NaOH solution, and the impure aluminum can be completely removed after filtering.
[0017] Furthermore, the selection and molar ratio of the molten salt in step S2 are LiOH:Li2CO3:KCl=0.84x:0.16x:(1-x), x=0.5-0.7.
[0018] Furthermore, in step S2, the molar ratio of the total amount of lithium ions in the molten salt to the amount of lithium ions lost in the positive electrode powder is 1:1-8:1;
[0019] And / or, in step S2, the volume ratio of the molten salt to the positive electrode powder should be 1:1-4:1 to ensure that the molten salt can fully cover the positive electrode powder after grinding.
[0020] Furthermore, in step S2, the ball mill rotates at a speed of 400-500 r / min, grinding for 20-30 min, and dispersant ethanol is added for full grinding;
[0021] And / or, the main components of the binder and the conductive agent mentioned in step S2 are polyvinylidene fluoride and carbon black, which will decompose when heated to a temperature above 800°C.
[0022] Furthermore, since the molten salts selected in step S2 are all water-soluble salts, residual molten salts can be effectively removed by filtering with deionized water in step S3.
[0023] Furthermore, the heat treatment temperature in step S3 is 600-800° C., and an oxidizing gas atmosphere such as oxygen is selected.
[0024] Furthermore, this molten salt method is applicable to layered nickel-cobalt-manganese ternary lithium-ion battery positive electrodes with different transition metal element ratios, such as NCM523, NCM622 and NCM811, and the best repair effect can be achieved by changing the heating conditions.
[0025] A highly degradable layered nickel-cobalt-manganese positive electrode material is prepared by the above-mentioned single crystal upgrading and reconstruction method of a highly degradable layered nickel-cobalt-manganese positive electrode material with the assistance of high-energy molten salt.
[0026] A lithium-ion battery comprises a battery positive electrode made of the above-mentioned highly degradable layered nickel-cobalt-manganese positive electrode material.
[0027] Compared with the conventional eutectic molten salt regeneration technology, the present invention has the following beneficial effects:
[0028] (1) The molten salt single crystal reconstruction method of the highly degradable layered nickel-cobalt-manganese positive electrode material provided by the present invention abandons the advantage of the conventional molten salt method in completing lithium replenishment under medium and low temperature conditions, but chooses to use the high-energy melting environment of the molten salt under high temperature conditions to achieve a high level of repair and regeneration of the discarded ternary lithium battery positive electrode material. When the temperature rises, on the one hand, it can accelerate the conduction and transportation process of the reaction ions in the molten salt environment, and the lithium replenishment process is more efficient and thorough, greatly reducing the reaction time and improving industrial production efficiency. On the other hand, the volatilization of the molten salt at high temperature can be used as a driving force for the regeneration and growth of the positive electrode particles. At the same time, under the action of the co-solvent KCl, it can ensure that the molten salt provides the driving force for the growth of the single crystal particles while maintaining the stability and uniformity of the entire molten salt lithium replenishment environment. Under the action of high-temperature molten salt, all defects of the waste positive electrode material are effectively restored, and the regenerated single crystal structure has better structural stability and excellent electrochemical properties.
[0029] (2) Compared with the conventional eutectic molten salt method, the molten salt single crystal reconstruction method for highly degradable layered nickel-cobalt-manganese positive electrode materials provided by the present invention has the following optimizations: first, molten salt regeneration performed only at the eutectic point temperature is not sufficient to completely repair all defects of highly degradable materials, while repair performed at a higher temperature can ensure that defect repair has sufficient driving force, and even positive electrode samples with serious defects can be fully restored after regeneration; second, the inevitable volatilization of molten salt at high temperature is also well solved in the present invention. Under the action of KCl, the volatilization is suppressed within an acceptable range, and the entire lithium replenishment environment is sufficient to ensure the regeneration of waste materials; finally, while repairing the defects, the final sample obtained by the molten salt single crystal reconstruction method provided by the present invention successfully grows into a single crystal structure with better stability, which greatly improves the capacity retention rate during the battery cycle, and is even better than standard commercial products.
[0030] (3) The molten salt single crystal reconstruction method of the highly degradable layered nickel-cobalt-manganese positive electrode material provided by the present invention has obvious advantages over the traditional indirect recovery method: almost no toxic and harmful gases are generated during the recovery process, and no organic waste liquid is generated, which is environmentally friendly; the molten salt raw materials are all cheap and clean inorganic metal salts, and the production cost is low; in addition, the entire process does not have complicated processing steps, and the main operations only include basic pretreatment, molten salt lithium supplementation and heat treatment, which is simple and efficient to operate; finally, as a direct recovery method, there is no need to consider the purification and separation of various metal elements in the waste positive electrode materials, but to achieve the recycling of waste batteries in the most ideal closed-loop recovery method.
[0031] (4) The molten salt single crystal reconstruction method of the highly degradable layered nickel-cobalt-manganese positive electrode material provided by the present invention can greatly simplify the pretreatment process of the battery. It only needs to separate the positive electrode material and the aluminum foil. The remaining other components such as PVDF, conductive carbon and electrolyte decomposition product LiF can decompose by themselves in a high-temperature molten salt environment and will not affect the performance of the regenerated positive electrode.
[0032] (5) The molten salt single crystal reconstruction method of the highly degradable layered nickel-cobalt-manganese positive electrode material provided by the present invention can comprehensively repair various defects in waste positive electrode materials. Various positive electrode failure causes such as active lithium loss, structural phase change, oxygen vacancies and cation mixing can be effectively eliminated in a high-temperature molten salt environment.
[0033] (6) The molten salt single crystal reconstruction method of the highly degradable layered nickel-cobalt-manganese positive electrode material provided by the present invention is the best measure to cope with the resource recycling under the dual carbon background. It can effectively solve the environmental pressure and economic burden brought by the peak of lithium-ion battery retirement, and at the same time achieve low-cost recycling and resource reuse.
[0034] (7) The molten salt single crystal reconstruction method of the highly degradable layered nickel-cobalt-manganese positive electrode material provided by the present invention has good universality and flexibility, and can be applied to retired positive electrode materials of lithium-ion batteries with various transition metal ratios (such as NCM523, NCM622, NCM811, etc.). It only needs to formulate different heating schemes according to different materials to achieve direct repair of waste positive electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 , 2XRD comparison diagram of the repaired regenerated samples (R-NCM, r-NCM) in implementation cases 1 and 2, the untreated samples (S-NCM) and the commercial samples (C-NCM).
[0037] Figure 3 XRD refinement diagrams of various samples in implementation cases 1 and 2.
[0038] Figure 4 SEM images of various materials in implementation cases 1 and 2.
[0039] Figure 5 Electrochemical cycle diagrams of various samples in implementation cases 1 and 2.
[0040] Figure 6 Electrochemical rate diagrams of various samples in implementation cases 1 and 2.
[0041] Figure 7 The capacity-voltage comparison diagram of various samples in implementation cases 1 and 2.
[0042] Figure 8 XPS spectra of Ni and O of various samples in implementation cases 1 and 2.
[0043] Fig. 9 Actual pictures of the operations in Cases 1 and 2 and actual pictures of samples after lithium supplementation with high-temperature molten salt.
[0044] Fig.10 This is a comparison of the XRD patterns of the samples after repair and regeneration in Cases 3 and 4.
[0045] Fig.11 This is a SEM comparison of the samples after repair and regeneration in implementation cases 3 and 4.
[0046] Fig.12 The electrochemical performance diagram of the regenerated samples in implementation cases 3 and 4.
[0047] Fig.13 XRD and refined images of the regenerated sample in implementation case 5.
[0048] Fig.14 This is the SEM image of the regenerated sample in implementation case 5.
[0049] Fig.15 This is the electrochemical cycle diagram of the regenerated sample in implementation case 5.
[0050] Fig.16 This is a SEM comparison image of the samples after repair and regeneration in implementation cases 6 and 7.
[0051] Fig.17 Electrochemical cycle diagram of the regenerated samples in implementation cases 6 and 7. DETAILED DESCRIPTION
[0052] In order to enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention and to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are further described below.
[0053] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0054] Implementation Case 1
[0055] (1) After being completely discharged in a Na2SO4 solution, the waste commercial NCM523 battery was disassembled to obtain an aluminum foil loaded with positive electrode active material. After drying in a drying oven, the aluminum foil was crushed using a crusher, and the positive electrode powder and the aluminum foil were separated using a 400-mesh sieve. The positive electrode powder to be recycled was then collected and recorded as S-NCM.
[0056] (2) Weigh 1 g of the powder in (1) (lithium loss is 41.3%), then add a specific ratio of eutectic molten salt and co-solvent (molar ratio of LiOH:Li2CO3:KCl=0.84x:0.16x:1-x, x=0.5), specifically weigh 0.42 g, 0.14 g and 0.88 g of LiOH.H2O, Li2CO3 and KCl respectively, then mix the S-NCM powder and molten salt-co-solvent and put them into a ball mill for grinding for 20 min at a speed of 400 r / min, and add dispersant ethanol to ensure that the powder to be recovered is completely and evenly distributed in the molten salt system. At the same time, the initial polycrystalline structure is broken to a certain extent, which is more conducive to the generation of single crystal structure in the regeneration reaction. After ball milling is completed and dried, the mixture is placed in an Al2O3 crucible.
[0057] (3) The crucible in (2) was placed in a muffle furnace for heating, and a gradient heating method was used to ensure the sufficiency of the reaction. The temperature was first raised to 600°C and kept for 2 hours, and then heated to 910°C and kept for 6 hours. The heating rate was 4°C / min, and the gas atmosphere was air. After heating, the sample was filtered through deionized water to remove residual lithium salts and co-solvents, and then the powder material was placed in a drying oven at 60°C and dried for 8 hours.
[0058] (4) Calculate the molar weight of the sample after drying, add about 5% molar ratio of Li2CO3, mix well with a mortar, and put it into an Al2O3 crucible. To ensure that the impurity phase structure that hinders the diffusion of lithium ions is completely restored to a layered structure, it is then kept at 600℃ in a tube furnace under an O2 atmosphere for 4 hours, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as R-NCM.
[0059] (5) The above powder samples were subjected to XRD, SEM and XPS tests. After the powders were made into slurry and assembled into half-cells, the electrochemical data of the cells were tested.
[0060] Implementation Case 2
[0061] (1) Weigh 1 g of the powder of (1) in Implementation Case 1 (lithium loss is 41.3%), and then add a specific proportion of eutectic molten salt (molar ratio of LiOH:Li2CO3=0.84:0.16). Compared with Case 1, no co-solvent KCl is added in this case to explore its role in the molten salt system. LiOH.H2O, Li2CO3 0.42 g and 0.14 g are weighed respectively, and then the S-NCM powder and the molten salt are mixed evenly using a ball mill.
[0062] (2) The crucible in (1) was placed in a muffle furnace and heated, first to 600°C and kept at this temperature for 2 h, then heated to 910°C and kept at this temperature for 6 h, with a heating rate of 4°C / min, and the gas atmosphere was air. After heating, the residual molten salt was removed by filtration with deionized water, and then placed in a drying oven and dried at 60°C for 8 h.
[0063] (3) Calculate the molar weight of the sample after drying, add about 5% molar ratio of Li2CO3, mix well with a mortar, and put into an Al2O3 crucible. Then, keep it at 600℃ for 4h in a tube furnace under O2 atmosphere, with a heating rate of 4℃ / min, so as to restore the impurity phase structure in the degraded powder. The sample after heat treatment is the repaired positive electrode powder, recorded as r-NCM.
[0064] (4) The powder samples were subjected to XRD, SEM and XPS tests. The powders were made into slurry and assembled into half-cells, and the electrochemical data of the cells were tested.
[0065] Figure 1 , 2The XRD comparison diagram of the regenerated samples (R-NCM, r-NCM) after repair in implementation cases 1 and 2, the untreated samples (S-NCM) and the commercial samples (C-NCM). It can be seen from the figure that all four samples are α-NaFeO2 layered structures (R-3m space group). By comparison, it can be seen that the (003) peak intensity of S-NCM is relatively low, indicating that the cations in the sample before treatment are seriously mixed. After regeneration and repair, combined with the data in Table 2, it can be seen that the I (003) / (104) values of R-NCM and r-NCM are significantly increased, almost at the same level as C-NCM, indicating that the regenerated samples have a good layered structure; in addition, the (003) peak of the treated sample migrates to a low angle, and the unit cell expands along the c-axis direction, indicating that due to Li + The crystal structure collapse caused by the loss was restored, and the degeneracy of the (108) and (110) peaks further confirmed that the Li vacancies in the regenerated sample were effectively replenished under the action of high-temperature molten salt.
[0066] Figure 3 The XRD refinement diagrams of various samples in implementation cases 1 and 2 are shown in Table 1 and Table 2. It can be seen that compared with the untreated S-NCM powder, the unit cell parameter c values of the regenerated R-NCM and r-NCM are increased, which confirms that the Li vacancies in both implementation cases are effectively supplemented, but the a value in r-NCM is reduced, while the a value in R-NCM is increased, which indicates that there are still Ni with smaller ionic radius in r-NCM. 2+ / Ni 3+ The Li / Ni mixing data in Table 1 also confirm the situation of occupying the Li position. Therefore, in Implementation Case 2, although the high-temperature molten salt without KCl can also replenish the Li loss in S-NCM, due to the rapid volatilization of LiOH+Li2CO3, the final repair degree is limited, and the degree of cation mixing is still at a high level; on the contrary, in Implementation Case 1, under the action of KCl stabilizing the molten salt environment, the crystal structure of the regenerated R-NCM is fully restored, and all performances are close to those of C-NCM materials.
[0067] Table 1: XRD refinement data of various samples in implementation cases 1 and 2
[0068]
[0069] Table 2: XRD peak (003) / (104) intensity ratios of various samples in implementation cases 1 and 2
[0070]
[0071] Figure 4The SEM images of various materials in implementation cases 1 and 2 show that the particle surface of the S-NCM sample is rough and finely broken, and there are impurities such as conductive carbon and PVDF between the particles. The R-NCM material repaired in implementation case 1 not only has a smooth particle surface and uniform size, but also compared with the secondary spherical particles of C-NCM, under the action of high-temperature molten salt, the particles grow into a more stable single crystal structure, avoiding the generation of intercrystalline cracks. Compared with the r-NCM material in implementation case 2, it can be clearly seen that the particle size is extremely uneven. Due to the unstable growth driving force provided by the rapid volatilization of the molten salt, a small amount of particles grow abnormally, and there are still small particles similar to those in S-NCM. Therefore, a stable and uniform molten salt environment is a key factor in effectively repairing the particle morphology. Under the fluxing and stabilizing effect of KCl, the eutectic system of LiOH+Li2CO3 is more gentle at high temperatures, which not only provides a stable medium transfer environment, but also ensures the uniformity of particle growth.
[0072] Table 3: Electrochemical data of various samples in implementation cases 1 and 2
[0073]
[0074] Figure 5 , 6 7 are comparison diagrams of the electrochemical performance of various samples in implementation cases 1 and 2. First, the constant current charge and discharge performance of the repaired materials under the two implementation cases was tested. Figure 5 As can be seen from the data given in Table 3, the R-NCM sample repaired by the synergistic effect of LiOH+Li2CO3+KCl in Implementation Case 1 has the best cycle stability, and still has a capacity retention rate of 81.2% after 200 cycles of charge and discharge at a 1C rate, which is significantly higher than the r-NCM material repaired only under the LiOH+Li2CO3 eutectic conditions in Implementation Case 2 (56.1% in 200 cycles). It is worth mentioning that although the first cycle capacity of R-NCM (156.8mAh / g) is slightly lower than that of C-NCM material (157.7mAh / g), in the subsequent cycle process, the capacity attenuation rate of the former is significantly lower than that of commercial powder (75.1% in 200 cycles), which is due to the more stable single crystal structure of R-NCM, further confirming that molten salt repair at high temperature can effectively improve the regeneration performance of waste positive electrode materials. Comparison Figure 6From the rate performance test graph, we can find that at different charge and discharge rates, R-NCM has a discharge capacity that is not inferior to C-NCM. At the same time, after a high-rate cycle of 5C, both can still recover to the initial level at 0.1C. Compared with the r-NCM and untreated S-NCM materials in Implementation Case 2, the capacity gap at different rates is more obvious, which fully proves the key stabilizing role of KCl in the entire molten salt system under high temperature conditions. Figure 7 The capacity-voltage diagram can more intuitively compare the capacity decay rate and cycle stability of different materials. As the number of battery cycles increases, the image curve of r-NCM in Implementation Case 2 gradually deforms, and the cycle stability is significantly reduced. Compared with R-NCM in Implementation Case 1, the difference is very significant. Although the capacity of R-NCM is constantly decaying during the cycle, its charge and discharge curve remains regular, and its capacity decreases the slowest among several materials. By comparing various electrochemical properties, R-NCM in Implementation Case 1 has the best comprehensive performance. Under the action of high-temperature molten salt, the lost Li + After replenishment, the capacity is restored to the same level as C-NCM. In addition, due to its unique single crystal structure, it is even better than C-NCM in cycle stability performance; in Implementation Case 2, although the capacity of r-NCM is improved compared to S-NCM, all performances have not reached the qualified level. The rapidly volatilizing eutectic molten salt cannot provide an ideal repair environment, resulting in the final regeneration effect being significantly inferior to R-NCM. Although high-temperature conditions can achieve high-level regeneration, a stable regeneration environment is also an indispensable element. In summary, traditional eutectic molten salts cannot directly adapt to the volatilization effect under high-temperature conditions, making it difficult to achieve an ideal repair effect. The LiOH+Li2CO3+KCl regeneration system proposed in this patent not only effectively alleviates the uncontrollable volatilization process of molten salts under high-temperature conditions, but also achieves high-level repair and regeneration of waste positive electrode materials with the help of a high-energy environment at a higher temperature.
[0075] Figure 8 The XPS spectra of Ni and O of various samples in implementation cases 1 and 2. It can be seen from the figure that Ni 2+ The proportion is 52.8%, while Ni 3+ The content is only 41.2%, which indicates that there is a large amount of NiO rock salt impurity phase on the surface of the waste material. This is due to the appearance of Li vacancies, which leads to Ni 2+ Irreversibly migrates to the surface of the material through the Li layer and combines with lattice oxygen to form a barrier to Li + The migrated spinel phase and rock salt phase hinder the diffusion channel of lithium ions and deteriorate the electrochemical performance of the material. 2+ / Ni 3+The change in the proportion of can be used to analyze the degree of repair of the material's crystal structure. After the repair of implementation cases 1 and 2, the Ni 2+ / Ni 3+ The proportions are 41.8% / 58.2% and 53.5% / 46.5% respectively. Ni in R-NCM 2+ The content of Ni ions in the r-NCM in case 2 did not change significantly, which shows that the impurities on the surface of the regenerated sample in case 1 have been effectively eliminated, and Li + The diffusion channel was successfully restored, corresponding to the significant improvement of the electrochemical performance of R-NCM; however, there are still a large number of non-layered phase structures in r-NCM. + The transport process of NCM is hindered, so the electrochemical performance is obviously inferior to that of R-NCM.
[0076] Fig. 9 The actual operation pictures in implementation cases 1 and 2 and the actual pictures of the samples after high-temperature molten salt lithium supplementation. The upper part of the figure is the flow chart of the entire implementation case. The waste positive electrode powder containing conductive carbon and binder is obtained by simple pretreatment and disassembly, and then mixed evenly with molten salt. Residual impurities are removed at the same time during the high-temperature lithium supplementation process, and finally the layered structure of the material is further repaired by heat treatment under O2 atmosphere to obtain a regenerated sample. It can be seen from the actual picture of the sample after lithium supplementation that in Example 2, due to the lack of KCl, the molten salt in the eutectic system of LiOH+Li2CO3 volatilizes rapidly, resulting in the final sample being in a block-like sintered state, while the sample after molten salt regeneration through the synergistic effect of LiOH+Li2CO3+KCl has a condensed state after melting and cooling. The process of molten salt lithium replenishment in Cases 1 and 2 can be judged from simple morphological analysis. Due to the addition of KCl, the molten salt environment in Case 1 becomes more stable and uniform, and the medium transfer process in the high-temperature molten state is more sufficient and efficient. In Case 2, due to the rapid volatilization loss of the low eutectic point LiOH+Li2CO3 system at a higher temperature, the entire process is similar to the traditional solid-state sintering method. At the same time, due to the molten salt volatilization, sufficient lithium source replenishment cannot be guaranteed, which ultimately leads to poor regeneration effect. By comparing the different experimental results in Cases 1 and 2, it can be clearly seen that KCl plays a key role in high-temperature molten salts. Only under the synergistic effect of high temperature conditions and the stable high-energy molten salt environment of KCl can the efficient regeneration and recycling of waste positive electrode materials be achieved.
[0077] Implementation Case 3
[0078] (1) Weigh 1 g of the powder of (1) in Example 1 (lithium loss is 41.3%), then add a specific ratio of eutectic molten salt and co-solvent (molar ratio of LiOH:Li2CO3:KCl=0.84x:0.16x:1-x, x=0.5), specifically weigh 0.42 g, 0.14 g and 0.88 g of LiOH.H2O, Li2CO3 and KCl respectively, then mix the S-NCM powder and molten salt evenly, grind them in a ball mill for 20 min at a speed of 400 r / min, and put the mixture into an Al2O3 crucible after ball milling.
[0079] (2) The crucible in (1) was placed in a muffle furnace and heated, first to 600°C and kept for 2 h, then heated to 900°C and kept for 6 h, with a heating rate of 4°C / min, and the gas atmosphere was air. After heating, the residual molten salt was removed by filtration, and then placed in a drying oven at 60°C for 8 h.
[0080] (3) Calculate the molar weight of the sample after drying, add about 5% molar ratio of Li2CO3, mix well with a mortar, and put into an Al2O3 crucible. Then, keep it at 600℃ in a tube furnace under O2 atmosphere for 4h, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as R-NCM-2.
[0081] (4) The above powder samples were subjected to XRD and SEM tests. At the same time, the powders were made into slurry and assembled into half-cells, and the electrochemical data of the cells were tested.
[0082] Implementation Case 4
[0083] (1) Weigh 1 g of the powder of Example 1 (1) (lithium loss is 41.3%), then add a specific proportion of eutectic molten salt (molar ratio of LiOH:Li2CO3=0.84:0.16), specifically weigh 0.42 g of LiOH.H2O and 0.14 g of Li2CO3, then mix the S-NCM powder and the molten salt evenly, grind them in a ball mill for 20 min at a speed of 400 r / min, and put the mixture into an Al2O3 crucible after ball milling.
[0084] (2) The crucible in (1) was placed in a muffle furnace and heated, first to 600°C and kept for 2 h, then heated to 900°C and kept for 6 h, with a heating rate of 4°C / min, and the gas atmosphere was air. After heating, the residual molten salt was removed by filtration, and then the sample was placed in a drying oven at 60°C and dried for 8 h.
[0085] (3) Calculate the molar weight of the sample after drying, add about 5% molar ratio of Li2CO3, mix well with a mortar, and put into an Al2O3 crucible. Then, keep it at 600℃ in a tube furnace under O2 atmosphere for 4h, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as r-NCM-2.
[0086] (4) The above powder samples were subjected to XRD and SEM tests. At the same time, the powders were made into slurry and assembled into half-cells, and the electrochemical data of the cells were tested.
[0087] Fig.10 The XRD comparison diagram of the samples after repair and regeneration in implementation cases 3 and 4. Under the heating condition of 900℃, the crystal structure of R-NCM-2 is effectively restored, and the intensity ratio of I(003) / I(104) is greater than 1.2, indicating that the regenerated sample has a very standard layered structure. At the same time, the splitting degree of (108) and (110) peaks also confirms that the Li loss in the sample has been successfully supplemented; it is worth noting that in r-NCM-2, compared with the lithium supplementation process at 910℃, when the temperature is reduced, the layered structure of the regenerated sample is not well restored. The intensity ratio of (003) peak to (104) peak is only 1.06, which is lower than the standard value (1.2) recorded in the literature. In addition, the double peaks of (108) and (110) are also significantly split, indicating that the sample may still be in a lithium-deficient state at this time. Secondly, the fluctuation of the XRD curve is more obvious, proving that the crystallinity of the material is also poor. Therefore, the method in case 4 cannot achieve the expected regeneration effect.
[0088] Fig.11 The SEM images of the samples heated at 910℃ and 900℃ with or without KCl were compared. Under the same observation magnification, it can be intuitively found that the particle size at 910℃ is larger than that at 900℃, which proves that the temperature has a significant effect on the growth of particles. The higher the temperature, the more energy there is in the entire molten salt environment. + Faster transmission is also more conducive to particle growth, but once the upper temperature limit is exceeded, the rapid volatilization of the molten salt will inevitably lead to an imbalance in the molten environment and worsen the regeneration effect. Secondly, it can be seen from the figure that the surface of the R-NCM particles is smoother and the shape is more regular, which is very different from the particle morphology of r-NCM. Therefore, only the stable eutectic molten salt under the action of KCl can promote the uniform growth of particles and finally obtain a single crystal structure with superior performance.
[0089] Fig.12The electrochemical performance diagram of the regenerated samples in implementation cases 3 and 4. The difference in the cycle performance of the two regenerated samples is very obvious. Combined with the data in Table 4, it can be seen that the first cycle capacity of R-NCM-2 is 152.2 mAh / g, while the first cycle capacity of r-NCM-2 is only 122.9 mAh / g. After 100 cycles, R-NCM-2 still has a capacity retention rate of 87.2%, which is much higher than the 67.8% of r-NCM-2. At the same time, the rate performance of the two is also quite different, which further proves the key role of KCl under high temperature molten salt conditions. It is worth noting that the performance of the samples regenerated at 900°C in Cases 3 and 4 is lower than that of the samples regenerated at 910°C in Cases 1 and 2. However, compared with the first-cycle capacity of 103.2 mAh / g of the untreated sample, the heating condition of 900°C also played a role in lithium replenishment to a certain extent, but did not achieve the maximum optimization of the regeneration performance. Combined with the data of Case 1, it further shows that the final repair level of the sample can be improved at a higher temperature. Therefore, considering various factors, 910°C is the best high-temperature molten salt lithium replenishment temperature.
[0090] Table 4: Electrochemical data of regenerated samples and comparative samples of implementation cases 3 and 4
[0091]
[0092] Implementation Case 5
[0093] (1) Weigh 1 g of the powder of Example 1 (1) (lithium loss is 41.3%), then add a specific proportion of eutectic molten salt (molar ratio of LiOH:Li2CO3=0.84:0.16), specifically weigh 0.42 g of LiOH.H2O and 0.14 g of Li2CO3, then mix the S-NCM powder and the molten salt evenly, grind them in a ball mill for 20 min at a speed of 400 r / min, and put the mixture into an Al2O3 crucible after ball milling.
[0094] (2) The crucible in (1) was placed in a muffle furnace and heated at the eutectic temperature of LiOH:Li2CO3, 440°C, for 12 h, with a heating rate of 4°C / min and an air atmosphere. After heating, the residual molten salt was removed by filtration, and then placed in a drying oven at 60°C for 8 h.
[0095] (3) Calculate the molar weight of the sample after drying, add about 5% molar ratio of Li2CO3, mix well with a mortar, and put into an Al2O3 crucible. Then, keep it at 600℃ in a tube furnace under O2 atmosphere for 4h, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as r-NCM-3.
[0096] (4) The above powder samples were subjected to XRD and SEM tests. After the powders were made into slurry and assembled into half-cells, the electrochemical data of the cells were tested.
[0097] Table 5: XRD refinement data of regenerated samples and comparative samples in implementation case 5
[0098]
[0099]
[0100] Table 6: Electrochemical data of regenerated samples and comparative samples of implementation case 5
[0101]
[0102] Fig.13 The XRD and corresponding refined images of the regenerated sample in implementation case 5. Combined with the data in Table 5, it can be obtained that when the molten salt lithium is replenished at the eutectic point temperature of LiOH+Li2CO3, although the values of the unit cell parameters a and c are consistent with the change trend of lithium replenishment under high temperature conditions, and are increased compared with S-NCM, its I(003) / (104) value is 1.18, which does not reach the standard of 1.2, and the layered structure is not fully restored. In addition, the degree of cation mixing is 5.9% after repair, which is also higher than the 4.1% after regeneration treatment in case 1. This shows that although the regeneration reaction carried out at medium and low temperatures can play a certain repair role, the repair level is not as good as the high temperature and high energy lithium replenishment environment in case 1.
[0103] Fig.14 This is the SEM image of the regenerated sample in implementation case 5. At different magnifications, it can be seen that there are still many incomplete spherical secondary particles in the regenerated sample. This is the result of the increase in cracks and final particle breakage after the battery has been cycled for a long time. After the lithium supplementation reaction at 440°C, these degraded particles were not effectively repaired, but continued to exist between the particles in a broken form. Compared with all the uniform and regular single crystal particles in Case 1, this broken structure will inevitably lead to a decrease in battery performance. This shows that under the condition of 440°C, the growth driving force provided by the entire molten salt environment is very limited, and it can neither repair the complete secondary particles nor fully grow into a single crystal structure.
[0104] Fig.15This is the electrochemical performance diagram of the regenerated sample in Implementation Case 5. From the 100-cycle cycle data in the figure, it can be seen that the performance of the regenerated sample after the 440°C lithium supplementation reaction has been restored to a certain extent. At a charge and discharge rate of 1C, the first cycle capacity reaches 154.8 mAh / g, which shows that in the case of lithium loss, the molten salt at medium and low temperatures can achieve the lithium supplementation process. However, in the subsequent cycle process, it can be found that the capacity decreases very rapidly. At 100 cycles, the capacity is only 117.5 mAh / g, and the capacity retention rate is 75.8%, which is much lower than the 93.4% capacity retention rate of 100 cycles in Implementation Case 1. This may be related to the particle morphology observed in the SEM image. Due to the presence of broken particles, the structure of the material becomes very unstable during the charge and discharge process, and the irreversible volume strain and crack generation ultimately lead to a decrease in the electrochemical performance of the regenerated sample. Therefore, although the regeneration reaction carried out at the LiOH+Li2CO3 eutectic point temperature can repair the defects of S-NCM such as particle cracking, lithium loss and cation mixing during the long cycle process to a certain extent, the performance of the final material cannot achieve the expected effect. On the contrary, when the temperature is raised to 910°C and KCl is added at the same time to prevent the rapid volatilization of the molten salt and stabilize the lithium replenishment environment, it will not only completely repair all kinds of defects in S-NCM, but its electrochemical performance will also be comparable to that of commercial powders.
[0105] Implementation Case 6
[0106] (1) Weigh 1 g of the powder of Example 1 (1) (lithium loss is 41.3%), then add a specific proportion of eutectic molten salt (molar ratio of LiOH:Li2CO3:KCl=0.84x:0.16x:1-x, x=0.5), specifically weigh 0.42 g, 0.14 g and 0.88 g of LiOH.H2O, Li2CO3 and KCl respectively, then mix the S-NCM powder and the molten salt evenly, grind them in a ball mill for 20 min at a speed of 400 r / min, and put the mixture into an Al2O3 crucible after ball milling.
[0107] (2) The crucible in (1) was placed in a muffle furnace and heated, first to 600°C and kept for 2 h, then heated to 950°C and kept for 6 h, with a heating rate of 4°C / min, and the gas atmosphere was air. After heating, the residual molten salt in the sample was removed by filtration, and then placed in a blast drying oven at 60°C for 8 h.
[0108] (3) Calculate the molar weight of the sample after drying, add 5% molar ratio of Li2CO3, mix well with a mortar, and put into an Al2O3 crucible. Then, keep it at 600℃ in a tube furnace under O2 atmosphere for 4h, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as R-NCM-3.
[0109] (4) The powder samples were subjected to SEM testing. After the powders were made into slurry and assembled into half-cells, the electrochemical data of the cells were tested.
[0110] Implementation Case 7
[0111] (1) Weigh 1 g of the powder of Example 1 (1) (lithium loss is 41.3%), then add a specific proportion of eutectic molten salt (molar ratio of LiOH:Li2CO3:KCl=0.84x:0.16x:1-x, x=0.5), specifically weigh 0.42 g, 0.14 g and 0.88 g of LiOH.H2O, Li2CO3 and KCl respectively, then mix the S-NCM powder and the molten salt evenly, grind them in a ball mill for 20 min at a speed of 400 r / min, and put the mixture into an Al2O3 crucible after ball milling.
[0112] (2) The crucible in (1) was placed in a muffle furnace and heated, first to 600°C and kept for 2 h, then heated to 930°C and kept for 6 h, with a heating rate of 4°C / min, and the gas atmosphere was air. After heating, the residual molten salt was removed by filtration with deionized water, and then placed in a drying oven and dried at 60°C for 8 h.
[0113] (3) Calculate the molar weight of the sample after drying, add 5% molar ratio of Li2CO3, mix well with a mortar, and put into an Al2O3 crucible. Then, keep it at 600℃ in a tube furnace under O2 atmosphere for 4h, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as R-NCM-4.
[0114] (4) The powder samples were subjected to SEM testing. After the powders were made into slurry and assembled into half-cells, the electrochemical data of the cells were tested.
[0115] Table 7: Electrochemical data of regenerated samples and comparative samples in implementation cases 6 and 7
[0116]
[0117]
[0118] Fig.16 , 17The SEM images of the regenerated samples in implementation cases 6 and 7. It can be seen from the figure that when the temperature rises to 950°C, the morphology of the regenerated particles shows a distorted structure similar to that in case 2. This extremely uneven growth is caused by the uncontrollable volatilization of the molten salt, which shows that the added KCl is not enough to alleviate the volatilization of the lithium salt. The unbalanced lithium replenishment environment leads to the coexistence of particles with huge size differences. However, the particle morphology treated at 930°C is still relatively regular, and the large and uniform single crystal particles ensure excellent electrochemical performance after regeneration. Fig.17 The electrochemical performance of the regenerated samples in the case was compared with that of the untreated samples. Under the heating condition of 950℃, the deteriorated particle morphology led to a sharp decrease in the regeneration performance. The capacity of 142.7mAh / g in the first cycle was much lower than the result of treatment at 910℃ in Case 1. At the same time, the capacity retention rate of only 71.8% after 100 cycles also proved the instability of the particle structure. On the contrary, the regenerated sample under the treatment condition of 930℃ not only had a capacity of 155.2mAh / g in the first cycle, but also had a capacity retention rate of 90.3% after 100 cycles. This case shows that the treatment condition of 950℃ has exceeded the upper limit of the stability of the high-temperature molten salt. At this time, the performance of the regenerated sample will be seriously reduced, while the regenerated sample under the treatment condition of 930℃ still has good electrochemical performance (155.2mAh / g / 90.3%). Combined with the experimental data in Case 1, it is confirmed that the regeneration temperature of 910-930℃ can optimize the regeneration performance of highly degraded lithium-ion ternary layered cathode materials to the greatest extent.
[0119] Implementation Case 8
[0120] (1) Weigh 1 g of the powder of (1) in Example 1 (lithium loss is 41.3%), then add a specific ratio of eutectic molten salt and co-solvent (molar ratio of LiOH:Li2CO3:KCl=0.84x:0.16x:1-x, x=0.7), specifically weigh 0.46 g, 0.15 g and 0.42 g of LiOH.H2O, Li2CO3 and KCl respectively, then mix the S-NCM powder and the molten salt-co-solvent and put them into a ball mill, grind for 20 min at a speed of 400 r / min, and add dispersant ethanol to ensure that the powder to be recovered is completely and evenly distributed in the molten salt system. At the same time, the initial polycrystalline structure is broken to a certain extent, which is more conducive to the generation of single crystal structure in the regeneration reaction. After ball milling is completed and dried, the mixture is placed in an Al2O3 crucible.
[0121] (2) The crucible in (1) was placed in a muffle furnace for heating, and a gradient heating method was used to ensure the sufficiency of the reaction. The temperature was first raised to 600°C and kept for 2 hours, and then heated to 910°C and kept for 6 hours. The heating rate was 4°C / min, and the gas atmosphere was air. After heating, the sample was filtered through deionized water to remove residual lithium salts and co-solvents, and then the powder material was placed in a drying oven at 60°C and dried for 8 hours.
[0122] (3) Calculate the molar weight of the sample after drying, add about 5% molar ratio of Li2CO3, mix well with a mortar, and put it into an Al2O3 crucible. To ensure that the impurity phase structure that hinders the diffusion of lithium ions is completely restored to a layered structure, it is then kept at 600℃ in a tube furnace under an O2 atmosphere for 4 hours, with a heating rate of 2℃ / min. The sample after heat treatment is the repaired positive electrode powder, recorded as R-NCM-5.
[0123] (4) After the powder is made into slurry and assembled into a half-cell, the electrochemical data of the battery are tested.
[0124] Table 8: Electrochemical data of regenerated samples and comparative samples in Example 8
[0125]
[0126] The electrochemical data of each sample in Case 8 are shown in Table 8. When the x value in the molten salt ratio increases, the content of the co-solvent KCl decreases. When x=0.7, the inhibitory effect on the volatilization of lithium salt at high temperature is also reduced. Compared with the electrochemical data of x=0.5 in Case 1, the first cycle capacity of R-NCM-5 is 153.6 mAh / g, slightly lower than 156.8 mAh / g, and the capacity retention rate of 100 cycles (88.1%) is also slightly lower than the commercial standard sample (88.6%), but its various performances are still significantly better than the untreated sample (109.8 mAh / g / 68.4%). This case shows that when the KCl content decreases, the volatilization effect of the lithium salt intensifies, affecting the electrochemical performance of the final regenerated sample. However, compared with the performance of S-NCM without adding KCl (126.7 mAh / g) in Case 2, the treatment conditions of Case 8 still have a great advantage. Therefore, under appropriate temperature conditions (910-930°C), when the molten salt ratio is LiOH:Li2CO3:KCl=0.84x:0.16x:1-x, x=0.5-0.7, excellent regeneration electrochemical performance can be obtained.
[0127] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention are still within the protection scope of the present invention.
Claims
1. A method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal state with the aid of high-energy molten salt, characterized in that: The steps include: Step S1, after the waste ternary lithium-ion battery is completely discharged, the aluminum current collector coated with the positive electrode active material is separated by mechanical disassembly, and the aluminum foil can be removed by simply sieving after crushing with a pulverizer to obtain a positive electrode powder with degraded performance; Step S2, mixing the obtained positive electrode powder with the selected molten salt in proportion, grinding with a ball mill to ensure that the molten salt and the recovered powder are evenly mixed, and then performing a lithium replenishment process under high temperature conditions, while the residual binder and conductive agent impurities in the positive electrode powder can also be effectively removed; The lithium replenishment heating conditions are to heat to 600°C and keep it for 2 hours, then keep it at 910-930°C for 4-6 hours, the heating rate is 4°C / min, the gas atmosphere is air, and the gradient heating method can provide a more stable lithium replenishment molten salt environment; Step S3, after the lithium supplementation is completed, the sample is centrifuged, washed and dried, and then heat-treated in an oxygen atmosphere to repair the impurity phase structure that may exist on the particle surface.
2. According to claim 1, a method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal with the assistance of a high-energy molten salt, characterized in that: The complete discharge process in step S1 is carried out in a Na2SO4 solution with a concentration of 5%-10% and the immersion time is 48-72 hours; And / or, after the aluminum foil is initially removed by sieving through a 400 mesh in step S1, the positive electrode powder is alkaline-soaked with a NaOH solution, and the impure aluminum can be completely removed after filtering.
3. According to claim 1, a method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal with the assistance of a high-energy molten salt, characterized in that: The selection and molar ratio of the molten salt in step S2 are LiOH:Li2CO3:KCl=0.84x:0.16x:(1-x), x=0.5-0.
7.
4. A method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to single crystal by high-energy molten salt according to claim 1 or 3, characterized in that: In step S2, the molar ratio of the total amount of lithium ions in the molten salt to the amount of lithium ions lost in the positive electrode powder is 1:1-8:1; And / or, in step S2, the volume ratio of the molten salt to the positive electrode powder should be 1:1-4:1 to ensure that the molten salt can fully cover the positive electrode powder after grinding.
5. The method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal state with the assistance of a high-energy molten salt according to claim 1, characterized in that: In step S2, the ball mill rotates at a speed of 400-500 r / min for 20-30 min, and dispersant ethanol is added for full grinding; And / or, the main components of the binder and the conductive agent mentioned in step S2 are polyvinylidene fluoride and carbon black, which will decompose when heated to a temperature above 800°C.
6. The method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal state with the assistance of a high-energy molten salt according to claim 1, characterized in that: Since the molten salts selected in step S2 are all water-soluble salts, residual molten salts can be effectively removed by filtering with deionized water in step S3.
7. The method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal state with the assistance of a high-energy molten salt according to claim 1, characterized in that: The heat treatment temperature in step S3 is 600-800° C., and an oxidizing gas atmosphere is selected.
8. The method for upgrading and reconstructing a highly degradable layered nickel-cobalt-manganese cathode material to a single crystal state with the assistance of a high-energy molten salt according to claim 1, characterized in that: This molten salt method is suitable for layered nickel-cobalt-manganese ternary lithium-ion battery positive electrodes with different transition metal element ratios, and the best repair effect can be achieved by changing the heating conditions.
9. A highly degradable layered nickel-cobalt-manganese cathode material, characterized in that: It is prepared by the single crystal upgrading and reconstruction method of highly degradable layered nickel-cobalt-manganese positive electrode material with the assistance of high-energy molten salt as described in any one of claims 1-8.
10. A lithium ion battery, characterized in that: It comprises a battery positive electrode made of the highly degradable layered nickel-cobalt-manganese positive electrode material described in claim 9.
Citation Information
Patent Citations
Direct repair method for waste ternary lithium battery positive electrode material and ternary positive electrode material prepared by direct repair method
CN114204013A
Recycling method and application of waste lithium ion battery positive electrode material
CN116093482A
Upgrading and recycling method of waste high-nickel ternary positive electrode material
CN118136999A
Method and apparatus for recovering valuable metal in lithium secondary battery electrode material
JP2003206132A
Cited By
Lithium ion battery positive electrode material regeneration method based on synergistic effect of doping and fused salt reconstruction
CN121149475A
